2021
DOI: 10.1007/s40271-021-00563-7
|View full text |Cite
|
Sign up to set email alerts
|

How Do People with Experience of Infertility Value Different Aspects of Assistive Reproductive Therapy? Results from a Multi-Country Discrete Choice Experiment

Abstract: Objectives Assistive reproductive therapies can help those who have difficulty conceiving but different forms of assistive reproductive therapies are associated with different treatment characteristics. We undertook a large, multinational discrete choice experiment to understand patient preferences for assistive reproductive therapies. Methods We administered an online discrete choice experiment with persons who had experience with subfertility or assistive reproductive therapies in the USA, UK, the Nordic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Comparing our results to the broader literature suggests that marginal WTP values for some attributes of fertility treatment are similar across countries. For instance, our study indicated a marginal WTP value of $383-$524 across income categories for a one percentage point increase in the treatment success rate, which is comparable to values reported for European countries [23,29,58]. Given that other studies used different fertility treatment attributes, a direct comparison of the marginal WTP values is often not possible.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Comparing our results to the broader literature suggests that marginal WTP values for some attributes of fertility treatment are similar across countries. For instance, our study indicated a marginal WTP value of $383-$524 across income categories for a one percentage point increase in the treatment success rate, which is comparable to values reported for European countries [23,29,58]. Given that other studies used different fertility treatment attributes, a direct comparison of the marginal WTP values is often not possible.…”
Section: Discussionsupporting
confidence: 60%
“…Several stated-preference DCEs that assessed preferences for fertility treatments have been published [19][20][21][22][23][24][25][26][27][28][29][30], of which some elicited marginal willingness-to-pay (WTP) values for different attributes of fertility treatment [21,23,[27][28][29][30] and, notably, one study comparing preferences across countries [29]. We are aware of only one application of DCEs to a fertility treatment context in Australia [28], which elicited taxpayer/societal preferences for fertility treatment and derived marginal WTP values for treatment attributes explored.…”
Section: Discrete Choice Experiments (Dces) In the Context Of Fertili...mentioning
confidence: 99%
“…The characteristics of included studies are described in Table 1 . Twelve studies had a DCE design ( Musters et al , 2011 ; van Empel et al , 2011 ; Huppelschoten et al , 2014 ; van den Wijngaard et al , 2014 , 2015 ; Weiss et al , 2017 ; Hendriks et al , 2019 ; Braam et al , 2020 ; Abdulrahim et al , 2021 ; Cornelisse et al , 2022 ; Skedgel et al , 2022 ; Keller et al , 2023 ), one study included both a DCE and a survey ( Hendriks et al , 2016 ), one was designed as CAs study ( Palumbo et al , 2011 ), and six were survey and/or interview studies ( Bayram et al , 2005 ; Steures et al , 2005 ; van Weert et al , 2007 ; Sills et al , 2012 ; Duthie et al , 2017 ; Stormlund et al , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 20 studies, 11 had been conducted in the Netherlands ( Bayram et al , 2005 ; Steures et al , 2005 ; van Weert et al , 2007 ; Musters et al , 2011 ; van Empel et al , 2011 ; Huppelschoten et al , 2014 ; van den Wijngaard et al , 2014 , 2015 ; Weiss et al , 2017 ; Braam et al , 2020 ; Cornelisse et al , 2022 ), two studies were conducted in both the Netherlands and Belgium ( Hendriks et al , 2016 , 2019 ), two studies were carried out in the USA ( Sills et al , 2012 ; Duthie et al , 2017 ), one in Australia ( Keller et al , 2023 ), one in the UK ( Abdulrahim et al , 2021 ), one in Denmark ( Stormlund et al , 2019 ), and one in Spain ( Palumbo et al , 2011 ). The largest study included multiple countries: the USA, the UK, Denmark, Norway, Sweden, Finland, Spain, and China ( Skedgel et al , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation